2020
DOI: 10.1111/jopy.12549
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal model of rejection sensitivity and internalizing symptoms: Testing emotion regulation deficits as a mechanism and outcome of symptoms

Abstract: Objective: Individuals who experience heightened rejection sensitivity (RS) are at greater risk of increased internalizing symptoms over time. This is especially so for adolescents and young adults, as this is a time of many social transitions and an average increase in such symptoms. Yet, little longitudinal research has explored specific mechanisms that may help explain how RS lends itself to increased symptomology during adolescence and young adulthood. In this study, we tested the summative effect of emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
4
12
0
1
Order By: Relevance
“…These findings suggest that rejection sensitivity is a unique risk factor for a high level of social anxiety symptoms across the early years of adolescence and can identify youth at risk of continued symptoms into middle to later adolescence. In particular, and consistent with theory and research on the risk that social-information biases present in the development of youth anxiety (Spence & Rapee, 2016), adolescents higher in rejection sensitivity are more likely to interpret neutral or ambiguous social cues as rejection, react strongly to overt experience of rejection, and become more distressed from these social interactions into the future (Downey & Feldman, 1996; Gardner et al, 2020; Zimmer-Gembeck, 2016). These findings support the relevance for continued examination of rejection sensitivity as another cognitive-affective risk factor for maintenance of, or increases in, social anxiety symptoms.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These findings suggest that rejection sensitivity is a unique risk factor for a high level of social anxiety symptoms across the early years of adolescence and can identify youth at risk of continued symptoms into middle to later adolescence. In particular, and consistent with theory and research on the risk that social-information biases present in the development of youth anxiety (Spence & Rapee, 2016), adolescents higher in rejection sensitivity are more likely to interpret neutral or ambiguous social cues as rejection, react strongly to overt experience of rejection, and become more distressed from these social interactions into the future (Downey & Feldman, 1996; Gardner et al, 2020; Zimmer-Gembeck, 2016). These findings support the relevance for continued examination of rejection sensitivity as another cognitive-affective risk factor for maintenance of, or increases in, social anxiety symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, rejection sensitivity has been described as a mechanism that explains why rejection experiences are associated with maladjustment in multiple domains (Downey & Feldman, 1996; Downey et al, 1998a), and rejection sensitivity does seem to have far-reaching negative implications for psychosocial adjustment (see Duffy et al, 2020 or Zimmer-Gembeck, 2016 for reviews). Most relevant to the current study, rejection sensitivity has been associated with more social anxiety among adolescents (Bowker et al, 2011; Ding et al, 2020), and rejection sensitivity has been identified as a predictor of increased symptoms across a short period of time during late adolescence and young adulthood (Gardner et al, 2020).…”
Section: Peer Rejection Rejection Sensitivity and Social Anxietymentioning
confidence: 91%
See 1 more Smart Citation
“…While the constructs are interrelated, and indeed, biased interpretation is referenced in the definition of SRS (i.e., the tendency to readily perceive rejection), there are components of SRS that do not map closely onto interpretation bias. For example, the emotional reaction that follows perceived or actual rejection may contribute to socioemotional disorder symptoms via a pathway other than interpretation bias, such as affective dysregulation (Gardner et al, 2020).…”
Section: Bias and Parenting In Young People's Symptoms Of Socio-emotional Disordersmentioning
confidence: 99%
“…Personaliti yang wujud dalam individu adalah sama ada bersesuaian dan tidak bersesuaian berdasarkan sifat yang dimilikinya itu (Gadbois, 2014). Personaliti dalam diri individu tidak dapat dipisahkan dan saling lengkap-melengkapi antara satu sama lain (Melanie & Modecki, 2020). Individu yang berpersonaliti kebiasaannya dipengaruhi oleh emosi dalam hal membuat keputusan dan tindakannya.…”
Section: Pengenalanunclassified